Is anterior decompression and fusion superior to laminoplasty for cervical myelopathy due to ossification of posterior longitudinal ligament? A systematic review and meta-analysis - Xu, Ping (J Spinal Cord Med, 2019)
Context: Considerable controversy exists over surgical procedures for ossification of the posterior longitudinal ligament (OPLL). Objective: The purpose of the meta-analysis was to compare the clinical outcome of anterior decompression and fusion (ADF) with laminoplasty (LAMP) in treatment of cervical myelopathy due to OPLL. Methods: PubMed, EMBASE and the Cochrane Register of Controlled Trials database were searched to identify potential clinical studies compared ADF with LAMP for cervical myelopathy owing to OPLL. We also manually searched the reference lists of articles and reviews for possible relevant studies. Thirteen studies with 1120 patients were included in our analysis. Subgroup analyses were performed by the canal occupying ratio of OPLL. Results: Overall, the mean preoperative Japanese Orthopaedic Association (JOA) score was similar between two groups. Compared with LAMP group, ADF group was higher at the mean postoperative JOA scores and mean recovery rate, reoperation rate, and longer at mean operation time. There was not significantly different in mean blood loss and complication rate between two groups. In subgroup analysis, ADF had a higher mean postoperative JOA score and recovery rate than LAMP in cases of OPLL with occupying ratios ≥ 50%, while those difference were not found in cases of OPLL with occupying ratios < 50%. Conclusion: ADF achieves better neurological improvement compared with LAMP in treatment of cervical myelopathy due to OPLL, especially in cases of OPLL with occupying ratios ≥ 50%. Complication rate is similar between two groups, but ADF can increase the risk of reoperation